The Effects of Nanochitosan Coating to Phenolic Compounds of Basil Leaf (Ocimum basilicum L) Extracts - Luntungan, Aldian H.; Mandey, Lucia C.; Rumengan, Inneke F. M.; Suptijah, Pipih (Pascasarjana Unsrat, 2017)
Basil leaf (O. basilicum L) could be developed as a herbal supplement due to its phenolic compounds which have antioxidant activity. Extract of this plant would be more effective as a natural antioxidant if it is coated with nanochitosan. Nanochitosan was prepared from the parrot fish (scarus sp) scale and chitosan of crab’s shell by gelatin ionic method. The purpose of this study was to determine the effects of the nanochitosan coating on phenolic content of basil leaves. The parameters tested were phenolic content of the basil leaf extracts and nanochitosan coated basil leaf extracts. The results show that the size’s average of nanochitosan from fish scales were in 657,4 nm. Phenolic compound was not detected in both the fishscale and crab’s shell derived chitosan. In the other hand, phenolic compound of the basil leaf extract showed the presence of phenol content of 34.38 mg/kg. In basil leaf extracts coated with nanochitosan from fish scales and nanochitosan of crab’s shell showed a phenolic content of 39.28 mg / kg and 57.44 mg/kg respectively. This suggests that synthesis of phenolic compound was induced when the extract of basil leaves was coated by nanochitosan.Keywords: basil leaves, chitosan, nanoparticles, phenolic compounds